Pengaruh Perendaman Air Pantai Dan Limbah Detergen Terhadap Kuat Tekan Dan Kuat Lentur Dinding Pasangan Bata Merah - Wicaksono, Oktavianto Arif Nur, Ir. Aliem Sudjatmiko, MT, Ir. Suhendro Trinugroho, MT (2015)
The case which bases this research is SNI 03-4164-1996, it is about test method and way of strength test on wall with putting red brick without plaster for sructural wall and SNI 03-4165-1996, it is about flexure test of wall with the red brick without plaster for structural wall. This research means to know how the effect soaking at the beach and detergent waste to the compressive strength and flexure strenght wall with red brick without mortar. This research uses a half of red brick used as including 3 samples with different locations. The red brick is from Kudus, Pati, dan Klaten, each sample in three shoakings, in pure water, beach water, and detergent waste. The sample has size 115 mm x 800 mm x 500 mm for a half of setting brick according to SNI. The research was done at the Civil Engineering Laboratory of Universitas Muhammadiyah Surakarta . The design with mortar is used 1:3 (cement : sand). The strength tes and flexure test with variation setting red brick done after putting in water until 14 days. The result fro Civil Engineering Laboratory of Universitas Muhammadiyah Surakarta shows that the pure water , beach water, and waste detergent with half of setting red brick has effet to compressive strength and flexure strength of setting red brick. From the research is known that red brick from Kudus has the highest compressive strength and flexure strength to pure water, beach water, and detergent waste compared with red brick from Pati dan Klaten. From the research is known that the beach water is water has salt content, so it will effect to the decreasing of compressive strength and flexure strength of red brick.